Tinjauan Hukum Pembagian Harta Waris Kepada Anak Angkat Tanpa Melihat Kedudukan Ahli Waris Utama - Dwi Kasih Maharani Taib; Nur Mohamad Kasim; Sri Nanang Meiske Kamba (Universitas Katolik Widya Karya Malang, 2023)
The aim of this research is to find out the juridical review and legal consequences for the distribution of inheritance to adopted children regardless of the position of the main heir. The method used is empirical juridical research with primary data obtained in the field and secondary data through literature studies and related regulations. The results of this study indicate that based on article 171 letter (c) KHI who becomes an heir must have a blood relationship with the heir, not being hindered by law to become an heir and article 209 paragraph (2) KHI for adopted children who do not receive a will is given a mandatory will 1/3 of the heir's inheritance. However, the facts on the ground are not in accordance with the provisions above, in fact the heir gives more inheritance to the adopted child than the main heir on the grounds that groups 2, 3, and 4 do not object, then the second heir states that the adopted child is older than his biological child. This reduces and closes the share of legal heirs. In adopting a child, it is done in the best interest of the child based on local customs and applicable laws and regulations. This fulfills the elements of article 39 paragraph (1) and article 171 letter (h) KHI. There are three legal consequences of the distribution of inheritance to adopted children, namely: 1) The distribution of inheritance has not been fulfilled in Article 209 paragraph (2) KHI 2) The rights and obligations have been fulfilled for adopted children according to Article 171 letter (h) KHI. However, the adopted child is constrained in terms of legitieme portie cannot sue the position of the main heir 3) Lineage relations, the adoptive parents have severed the lineage relationship of the adopted child with his biological parents where he uses the surname of his adoptive father. This contradicts QS-Al Ahzab: 4 and 5 and does not fulfill article 39 paragraph (2).